PERLINDUNGAN HUKUM TERHADAP HAK – HAK PRAMUGARA TRANSMETRO PEKANBARU BERDASARKAN UNDANG – UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - lasoma, Kalys khairy; ', Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Regional Regulation as implementing regulations that specifically regulates Traffic and Road Transportations in Pekanbaru is Regional Regulation Number 2 year of 2009 about Traffic and Transportations in Pekanbaru. Everyone who wants to open parking area outside the road parking facilities are required to have permission from the local government which is stated in Article 259 paragraph (1) Regional Regulation No. 2 year of 2009 about Traffic and Road Transportations in Pekanbaru. However, not everyone who is opening parking area facilities have the permission of the Local Government Pekanbaru.Based on the result of the research, there are three formulation of the problems. First, the implementation of the provisions of criminal or criminal prosecution against theoffenders of illegal parking management in junior high schools area has basically done, forms of crime has been given by the Department of Transportation, Communication, and informationsof Pekanbaru are not in accordance with what has been stated in Regional Regulation Pekanbaru No. 2 year of 2009 on Traffic and Road Transportations in Pekanbaru which are imprisonment and fine. However, only punishment of fines and penalties that are not in accordance with the Regional Regulations. Second, obstacles of the implementation of the penal provisions against the offenders of illegal parking management in junior high schools area in Warpoyan Damai district in terms of personnel, in terms of casualties, and the terms of their perpetrators.Third, the efforts are being made to overcome the barriers to the implementation of the penal provisions against theoffenders of illegal parking management in junior high schools area in the District of Marpoyan Damai is in terms of personnel, in terms of casualties, and the terms of their perpetrators.